Structural Equation Modeling on Health-related Quality of Life of Patients with Ankylosing Spondylitis - Ae Ri JANG; Keum Seong JANG (Tehran University of Medical Sciences, 2017)
Background: Ankylosing Spondylitis (AS) is a chronic, progressive, and inflammatory disease. The objective of this study was to construct a hypothetical model to determine factors affecting health-related quality of life (HRQOL) of AS patients (ASHRQOL). Methods: A survey was conducted on 275 patients who visited Chonnam National University Bitgoeul Hospital. Data of different variables were collected over two months in 2015. Results: A hypothetical model did not reach recommended level of fit verification. Therefore, health perception variable was eliminated on theoretical basis. Path between function and HRQOL was added after eliminating unimportant path before completing the final modified model. Conclusion: The final revised model met recommended levels of fit test except AGFI. The model explained 57.6% of ASQOL. Further study is needed to develop efficient interventional strategy for improving ASHRQOL.